The Effectiveness of Expansion of The Working Area of Land Deed Officials Related To Electronic Land Services - Lingga Felani; Miftakhul Huda (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2022)
Fulfillment of legality in legal relations and legal actions in the private sphere, the authority is given to public officials who are called PPAT. In terms of carrying out the duties of the PPAT, the aim is to provide a deed as evidence of a special legal action relating to land and buildings. To maximize this goal, the Government Regulation concerning PPAT Position Regulations was enacted in which there was an expansion of the working area into a provincial area and the convenience of electronic land information services. The existence of such expansion cannot be applied by PPAT. The formulation of the problem in this study is the effectiveness of the expansion of the PPAT's work area related to electronic land information services and the criteria for expanding the PPAT's work area that reflect legal certainty. The research method in this paper is normative juridical research. The research results obtained from this writing are that the expansion of the PPAT work area based on electronic land information services cannot run effectively because there is no coordination between Land Offices in other regions, differences in values in the application of BPHTB and no regulation regarding technical legal actions related to land in other work areas against PPAT and other parties.